Plant Iridoids Affect Intraocular Pressure and Vascular Flow in the Rabbit Eye - Dorota Szumny; Tomasz Sozański; Adam Szeląg; Antoni Szumny (Applied Sciences)
For plant-derived raw materials, there are very few studies regarding the effect of intraocular administration on intraocular pressure (IOP) and associated blood flow. Traditional folk medicine uses many natural resources for eye disorders. However, in the main, these exhibit an anti-inflammatory and moisturizing effect. The intraocular pressure reduction and neuroprotective effects are known, but only for orally administered products. In the work presented here, the effect of eight natural iridoids in concentrations of 0.1 and 0.5% in saline on IOP and blood flow in iris vessels was studied in white New Zealand rabbits. No ocular adverse effects were observed during the whole experiment. We demonstrated, for the first time, significant reductions in IOP for five of the eight iridoids tested at a concentration of 0.5%. These were verbenalin, aucubin, oleuropein, gentiopicroside, and secologanin. The highest effect of IOP lowering, a nearly 1.5 mmHg difference from baseline, was observed for verbenalin 2 h after administration. An increase in vascular inflow was observed only with the administration of aucubin, catalpol, and gentiopicroside at 2 and 3 h after administration of the 0.5% solution. This effect was contrary to the result for the reference—timolol—which significantly reduced flow by more than 100 flux during the first hours of the experiment. In summary, selected iridoids could be considered, after further investigation, as natural components for ophthalmic formulation in the prevention of eye diseases.